Body composition in 18‐ to 88‐year‐old adults—comparison of multifrequency bioimpedance and dual‐energy X‐ray absorptiometry. (5th September 2013) - Sillanpää, Elina; Cheng, Sulin; Häkkinen, Keijo; Finni, Taija; Walker, Simon; Pesola, Arto; Ahtiainen, Juha; Stenroth, Lauri; Selänne, Harri; Sipilä, Sarianna
Abstract : Objective: This study compared bioimpedance analysis (BIA) in the assessment of body composition with dual‐energy X‐ray absorptiometry (DXA) in 18‐ to 88‐year‐old adults. Design and Methods: Body composition of 882 adults was estimated by eight‐polar BIA and DXA. In addition, estimates of lean mass, fat mass, and percentage of fat were investigated across a range of age and leisure time physical activity (LTPA) groups. Results: Compared to DXA, larger lean masses (mean difference 2.9 and 1.6 kg) and smaller fat masses (3.1 and 2.6 kg) were estimated by BIA in both women and men, respectively. Differences between the methods' mean values were evident in all age and LTPA groups, except in the oldest men (over 70 years). Age, waist circumference, grip strength, and LTPA explained 21% or less of the variance observed in the differences between methods. Conclusions: Compared to DXA, BIA provided systematically different body composition estimates throughout the adult age span with considerable amount of intraindividual variation. The differences between estimates may be related to the BIAs' algorithm or body geometry or composition of the population used in this study. Knowledge about the methodological limitations and device comparability is essential for researchers, clinicians, and persons working in rehabilitation and sport centers.